Photo Catalytic Degradation of Coomassie Brilliant Blue Using a Ternary Polyaniline/ Fe2O3/Graphene Nano Composite Under Visible Light - Fares Fenniche; Yasmina Khane; Zoulikha Hafsi; Farhat , Masouda; Djaber Aouf; F. Alarbi (Sebha University Conference Proceedings, 2025)
This study reports the successful synthesis and comprehensive characterization of a novel ternary nano composite composed of polyaniline (PANI), iron oxide (Fe₂O₃), and graphene, tailored for efficient phot ocatalytic degradation of organic dyes under visible light, the nano composite was synthesized via an in-situ oxidative polymerization method, ensuring uniform dispersion of Fe₂O₃ nanoparticles and graphene sheets within the conductive PANI matrix. Structural and morphological analyses including spectroscopic and microscopic techniques confirmed effective integration of the three components and revealed a highly porous architecture favorable for enhanced photo catalytic activity, the photo catalytic performance was evaluated through the degradation of Coomassie Brilliant Blue (CBB) dye under visible light, with the ternary nano composite achieving a remarkable degradation efficiency of up to 95% within a short irradiation period. Furthermore, the material demonstrated excellent chemical stability and retained its activity over multiple reuse cycles, underscoring its practical applicability for sustainable wastewater treatment and environmental remediation. These findings emphasize the potential of hybrid nano composites integrating conductive polymers, metal oxides, and carbon nano materials as promising photo catalysts for addressing persistent organic pollutants..